Smart Grid – Introduction, Advantages and Implementation Status in India with a focus on Tamil Nadu: A Systematic Review. - Dr. G.MADHUMITA, R.RAJESH KANNAN (International Journal of Advanced Science and Technology, 2020)
This article talks about background and advantages of Smart Grid technology. Smart Grid as a concept is being contemplated by several countries since more than a decade now. Every country including India is at a different level of implementation. Rise of renewable sources of energy have changed the landscape of energy production & consumption. Consumers are given a chance to become prosumers in projects like rooftop solar plants etc. Such changes have blurred the distinction between power generation, distribution and transmission thereby pushing for a need of bidirectional inputs. Power Discoms have long suffered because of energy loss and theft in transmission. Several states have started replacing the traditional meters with smart meters and have already witnessed the positive changes in revenue realization. Complex grids and distribution systems make it difficult to bring all utilities to same platform and implement Smart Grid mission in a smooth manner. Government has high impetus on R&D and phase-wise implementation of smart grid, however achievement in the field is a far cry from the targets. This article also talks about status of implementation of Smart Grid in Tamil Nadu. Tamil Nadu is far ahead of any other state and also appear in Top 10 producer of renewable energy in the world. It is the only Asian market to appear in the list (Tim Buckley, IEEFA’s director of energy finance studies, Australasia, 2018). There have been initiatives from the state government to learn the smart grid technology from UK and use the learnings for establishing an effective energy system.